Fantasy baseball and mathematics : - Flockhart, Dan (Jossey-Bass, 2007)
Fantasy sports are a hit worldwide, and now teachers and parents can take advantage of this phenomenon to give students a reason to look forward to doing math. The games and activities in Fantasy Baseball and Mathematics will get kids excited about learning and practicing math, even if they're not big sports fans. With this fun-filled educational resource, you can teach one math concept or many, and plan lessons that can last for a week or a whole season. Here's how it works. Students create fantasy teams by picking real-life professional baseball players, and then follow their players' statistics and calculate their teams' total points using algebraic or nonalgebraic methods specifically designed to complement the math skills they're learning. The instructions are easy to follow and the dynamic hands-on games address all learning styles and abilities. The book includes more than 100 scoring systems that give you the flexibility to customize the content according to your students' skill levels.